Development Application for Computerized Maintenance Management System (CMMS) in the Central Sterile Supply Department ( CSSD ) and the Surgery Room - Widyananda, Rival; Sutanto, Teguh; Romeo, Romeo (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Department of Surgery is one of department at the Hospital that is important and are directly related to patient safety. The main business processes in the Department of Surgery consists of three processes, namely the sterilization process performed on unit Central Sterile Supply Department (CSSD), the process of asset preservation operations and management processes.Current problems now is asset preservation maintenance in the CSSD and the Operations Room at the RSPG as well as (1) an inventory of the equipment is not good, making it difficult for the Department of Surgery at tracking the existence of tools, (2) determine the condition of asset status if available or not available when needed, (3) how the track record / history medical equipment, (4) any device that is often susceptible to interference, and (5) how the records or documentation of results maintenance is performed. The solution to these problems is a CMMS application, where the application can CMMS asset inventory along with the location of assets, asset maintenance record of all processes in order to know the status of assets and asset maintenance history and generate documentation in the form of maintenance reports and provide information such as dashboard graphs asset care process.